FOREIGN BRAND ADMIRATION AMONG YOUNG CONSUMERS IN INDONESIA - Sulhaini*, Sulhaini; Sagir*, Junaidi; Sulaimiah*, Sulaimiah (Universitas Prasetiya Mulya, 2020)
This study extends the theoretical understanding of the positive and negative emotions of consumers towards foreign vs local brands by providing conceptualisation and measurement of foreign brand admiration and passive brand hate towards local brands. The study incorporates hedonic value dominance and home country image, which is the image of a consumer?s own country. The results show that young consumers in a developing country are both passive brand haters towards local brands and foreign brand admirers. When they possess an inferior image of their home country, they show admiration towards foreign brands. The positive emotion is however mainly influenced by hedonic value dominance, which also have a great contribution to passive brand hate toward local brands. As they have strong negative emotion, they tend to admire foreign brands that offer more hedonic values. In comparison to the negative emotion, the positive emotion indeed has a much stronger contribution toward willingness to pay more for foreign brands. The paper provides useful managerial implications for foreign brand and local brand owners to compete in the country?s market place.Keywords:Hedonic value dominance, Foreign brand admiration, Passive brand hate, Home country image* Department of Management, the University of Mataram. Jl. Majapahit No.62, Gomong, Kec. Selaparang, Kota Mataram, Nusa Tenggara Bar. 83115, Indonesia https://doi.org/10.21632/irjbs.13.1.33-47